Seguridad : crime, police power and democracy in Argentina - Seri, Guillermina (Continuum International Publishing Group, 2012)
"This study of police governance draws on over ninety interviews conducted with Argentine police officers. In Argentina, a rising fear of crime has led to the politics of Seguridad, a concept that amalgamates personal safety with state security. As a new governing rationale, Seguridad is strengthening forms of police intervention that weaken the democracy. As they target crime, the police have the power to deny rights, deciding whether an individual is a citizen or a criminal suspect -- the latter often being attributed to members of vulnerable groups. This study brings together key issues of governance that involve the police, democracy, and the quality of citizenship. It sheds light on how the police act as gatekeepers of citizenship and administrators of rights and law. Here, the rhetoric of Seguridad is seen as an ideological framework that masks inequality and unites 'good' citizens. Seguridad shows how police practices should be part of our understanding of regimes and will appeal to anyone concerned with security forces, as well as researchers in democratic theory and Latin American politics"--Provided by publisher.